MAIN PROBLEMS OF OPTIMIZING THE COMPANY'S CAPITAL STRUCTURE AND GLOBAL MODELS - ShukurovAdietulla; Niyazbayeva Aigul; Baimukasheva Zhanimgul; Balginova Kuralai; Kalaganova Nursulu (Academic Journal of Physical and Chemical Sciences, 2020)
Financial management is the process of productive use of financial resources, counting the budgetary relations of the enterprise, the inflow of cash flows, the provision of the required level of capital. Investment decisions are made in the placement of effective financial investments. Financial decisions are intended for decisions on the placement of funds, determining the composition and structure of capital, financing of long-term and shortterm resources, the ideal and efficient use of equity and debt capital. In a period of uncertainty and competition in the market, the optimization of the capital of the enterprise, its structure leads to the strengthening of the financial position, and negative financial decisions in the management of the capital structure lead to a slowdown of the enterprise. As a result of compelling capital management of the enterprise includes a combination of all financial, investment and operating cash flows, which has a positive impact on financial development. The role of financial management in the management of capital structure in an important financial mechanism is special. Improving the efficiency of capital structure management is also important in increasing the profitability of capital owners. In the conditions of market development, the study of optimization of financial management of capital in the enterprise and the disclosure of the impact of capital, financial management decisions on the financial activities of domestic enterprises play an important role and remain relevant. Entrepreneurship financing is aimed at ensuring the efficiency of financial management cash flow and working capital as a form of capital management. Capital structure management is a special system that determines the overall financial situation, cash flows, cash resources, the effective organization of financial relations. One of the areas of management in financial management is capital - the source of funding for the company, ie the liabilities on the balance sheet that bring income. The results of financial analysis are used as an information base for the analysis of the structure, assessment of the use of capital of the enterprise. The role of financial management decisions in managing the capital structure is growing in the development of competition in a market economy. In the current situation, enterprises need to determine the capital, resource potential, solvency in the management of financial decisions. This involves the optimization of financial relations, the capital of the enterprise and its structure, increasing the efficiency of management. If the indicators of the financial situation show profitability, financial success, the capital structure determines the efficient allocation of resources. The study of financial management in the field of capital management, the system of defining and improving the structure of capital is of interest to both financial partners and investors and creditors. The study of optimization of the capital structure of the enterprise is relevant today.